A Randomized Controlled Trial of the Effects of Mindfulness-Based Stress Reduction (MBSR[BC]) on Levels of Inflammatory Biomarkers Among Recovering Breast Cancer Survivors. (July 2017) - Reich, Richard R.; Lengacher, Cecile A.; Klein, Thomas W.; Newton, Cathy; Shivers, Steve; Ramesar, Sophia; Alinat, Carissa B.; Paterson, Carly; Le, Alice; Park, Jong Y.; Johnson-Mallard, Versie; Elias, Maya; et al.
Purpose: The purpose of this substudy of a large randomized controlled trial was to evaluate the efficacy of the Mindfulness-Based Stress Reduction (Breast Cancer) (MBSR[BC]) program compared to usual care (UC) in normalizing blood levels of pro-inflammatory cytokines among breast cancer survivors (BCS). Method: A total of 322 BCS were randomized to either a 6-week MBSR(BC) program or a UC. At baseline and 6 and 12 weeks, 10 ml of venous blood and demographic and clinical data were collected and/or updated. Plasma cytokines (interleukin [IL]-1β, IL-6, IL-10, tumor necrosis factor [TNF] α, transforming growth factor [TGF] β1, soluble tumor necrosis factor receptor [sTNFR] 1) were assayed. Linear mixed models were used to assess cytokine levels across three time points (baseline and 6 and 12 weeks) by group (MBSR[BC] vs. UC). Results: Of the six measured cytokines, three were nondetectable at rates greater than 50% (IL-10, IL-1β, TGF-β1) and, because of overall low prevalence, were not analyzed further. For the remaining cytokines (TNFα, IL-6, sTNFR1), results showed that TNFα and IL-6 increased during the follow-up period (between 6 and 12 weeks) rather than during the MBSR(BC) training period (between baseline and 6 weeks), while sTNFR1 levels did not change significantly across the 12-week period. Conclusions: Study results suggest that MBSR(BC) affects cytokine levels in BCS, mainly with increases in TNFα and IL-6. The data further suggest that B-cell modulation may be a part of immune recovery during breast cancer management and that increases in TNFα and IL-6 may be markers for MBSR(BC)-related recovery.